Children's Nutritional Status in terms of Dental Caries in Elementary School Students of GMIT Baumata: Status Gizi Anak Ditinjau dari Karies Gigi pada Siswa SD GMIT Baumata - Ade Irma Mantutu; Emma Krisyudhanti; Ferdinan Fankari; Christina Ngadilah (Poltekkes Kemenkes Kupang, 2020)
Nutritional disorders are caused by primary or secondary factors. The primary factor is when a person's food composition is wrong in quantity or quality caused by a lack of food supply, poor food distribution, poverty, ignorance, wrong eating habits and so on. Secondary factors include all factors that cause nutrients not to reach digestive cells such as bad teeth (dental caries). A person with a bad masticatory apparatus will choose food according to the strength of his chewing so that in the end it can lead to malnutrition. The purpose of this study was to determine the nutritional status of children in terms of dental caries in elementary school students at GMIT Baumata. This research method uses the description method, with a population of 100 students. The results showed that the nutritional status of students in the category of very thin 7%, underweight 52%, normal 41%, obese 0%, obese 0%, the condition of dental caries status of students 2 was 38%, 2 was 62% and nutritional status conditions in terms of student dental caries, namely the category of very thin nutrition with caries 2 is 0% while 2 is 7%, underweight nutrition category with caries 2 is 4% while 2 is 48%, normal nutrition category with caries 2 is 34 % while 2 is 7%, obese nutrition category with 2 caries is 0%, 2 is 0% and obesity nutrition category with 2 caries is 0%, 2 is 0%. The conclusion of this study is that the highest nutritional status of children is the category of underweight nutritional status and the highest dental caries condition is 2 or has not reached the national target. The nutritional status of children in terms of dental caries, the highest percentage is thin nutritional status with caries status 2 is 48%. Gangguan gizi disebabkan oleh faktor primer atau sekunder. Faktor primer adalah bila susunan makanan seseorang salah dalam kuantitas atau kualitas yang disebabkan oleh kurangnya penyediaan pangan, kurang baiknya distribusi pangan, kemiskinan, ketidaktahuan, kebiasaan makan yang salah dan sebagainya. Faktor sekunder meliputi semua faktor yang menyebabkan zat-zat gizi tidak sampai di sel-sel pencernaan seperti gigi-geligi yang tidak baik (karies gigi). Seseorang dengan alat pengunyahan yang tidak baik akan memilih makanan sesuai dengan kekuatan kunyahnya sehingga pada akhirnya dapat mengakibatkan malnutrisi. Tujuan penelitian ini adalah untuk mengetahui status gizi anak ditinjau dari karies gigi pada siswa SD GMIT Baumata. Metode penelitian ini menggunakan metode deskripsi, dengan populasi sebanyak 100 siswa. Hasil penelitian menunjukkan bahwa kondisi status gizi siswa kategori sangat kurus 7%, kurus 52%, normal 41%, gemuk 0%, obesitas 0%, kondisi status karies gigi siswa ≥2 adalah 38%, ≤2 adalah 62% dan kondisi status gizi ditinjau dari karies gigi siswa yaitu kategori gizi sangat kurus dengan karies ≥2 adalah 0% sedangkan ≤2 adalah 7%, kategori gizi kurus dengan karies ≥2 adalah 4% sedangkan ≤2 adalah 48%, kategori gizi normal dengan karies ≥2 adalah 34% sedangkan ≤2 adalah 7%, kategori gizi gemuk dengan karies ≥2 adalah 0%, ≤2 adalah 0% dan kategori gizi obesitas dengan karies ≥2 adalah 0%, ≤2 adalah 0%. Kesimpulan penelitian ini yaitu kondisi status gizi anak yang paling besar adalah kategori status gizi kurus dan kondisi karies gigi yang paling besar yaitu ≤2 atau belum mencapai target nasional. Status gizi anak ditinjau dari karies gigi yang paling besar presentasenya adalah status gizi Kurus dengan status karies ≤2 adalah 48%.